Raittijärvi-Kaijukan kylä - Kallio-Koski, Jyrki; Kallio-Koski, Anja; Suistola, Anja (Jyrki Kallio-Koski, 2017)
Oanádus.
Keywords: lapinkylät; saamelaisuus; saamelaiskulttuuri; saamelaiset; poronhoito; erämaa-alueet; historia; valokuvataide; dokumenttivalokuvaus; luonnonvalokuvaus; Raittijärvi (Enontekiö); Lappi